(untitled) (Journal of Economics and Sustainability, 2021)
Diabetes has become a serious public health concern. The objective of the present study is to examine the sociodemographic and lifestyle factors associated with consumption of sugar-sweetened food among different age groups of households in Malaysia. A nationally representative data (n = 14838) is used for secondary analysis. Multiple regressions are used to examine the independent effects of sociodemographic and lifestyle factors on household expenditure on sugar-sweetened food. Analyse are stratified by age group. Households headed by older individuals tend to spend more on sugar-sweetened food than households headed by younger individuals. Household size is positively associated with household consumption of sugar-sweetened food. Bumiputera households spend more on sugar-sweetened food than non-Bumiputera households. Sociodemographic and lifestyle factors play an important role in determining consumption of sugar-sweetened food. Policy makers should pay special attention to the types of households that consume a lot of sugar-sweetened food.